(untitled) (Philology, 2020)
This article analyzes the essence of interculturalism as a specific form of co-existence as well as a factor of key importance in modern society. Along with that, it reviews the reasons asking for inclusion of interculturalism in education. The focus of the discussion is upon various arguments showing that interculturalism is among the main features that make education capable of addressing the needs of today’s learners.